1979
DOI: 10.1111/j.1471-4159.1979.tb04579.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Activated Glutaminase Activity and Glutamine Uptake in Primary Cultures of Astrocytes

Abstract: Abstract— Uptake and release of glutamine were measured in primary cultures of astrocytes together with the activity of the phosphate activated glutaminase (EC 3.5.1.2). In contrast to previous findings of an effective, high affinity uptake of other amino acids (e.g. glutamate, GABA) no such uptake of glutamine was observed, though a saturable, concentrative uptake mechanism did exist (Km= 3.3 ± 0.5 mm; Vmax= 50.2 ± 12.6 nmol ± min−1± mg−1). The phosphate activated glutaminase activity in the astrocytes (6.9 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
66
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(74 citation statements)
references
References 42 publications
7
66
1
Order By: Relevance
“…23 Because our study was conducted with elevated and saturating blood glutamine concentrations, effectively reducing the effects of other competing amino acids, our estimate of V Gln(in) for physiologic blood glutamine level likely reflects an upper limit. Compared with the in vivo estimates, reported maximum rates of glutamine transport in cultured neurons and astrocytes are much higher (e.g., V max of 0.7 to 5.0 mmol/g per minute assuming 100 mg protein/g), [27][28][29] suggesting that the lower rates measured in vivo reflect mainly transport through the blood-brain barrier. Such comparisons, however, must be made with ample caution due to the incomplete understanding of transporter types involved, their physical properties (e.g., whether electrogenic or electroneutral, ionic dependencies, and potential for exchange), and the consequence of averaging over multiple transporter types and compartments reflected in the in vivo measurement.…”
Section: Comparison Of Glutamine Influx With Previously Reported Valuesmentioning
confidence: 65%
“…23 Because our study was conducted with elevated and saturating blood glutamine concentrations, effectively reducing the effects of other competing amino acids, our estimate of V Gln(in) for physiologic blood glutamine level likely reflects an upper limit. Compared with the in vivo estimates, reported maximum rates of glutamine transport in cultured neurons and astrocytes are much higher (e.g., V max of 0.7 to 5.0 mmol/g per minute assuming 100 mg protein/g), [27][28][29] suggesting that the lower rates measured in vivo reflect mainly transport through the blood-brain barrier. Such comparisons, however, must be made with ample caution due to the incomplete understanding of transporter types involved, their physical properties (e.g., whether electrogenic or electroneutral, ionic dependencies, and potential for exchange), and the consequence of averaging over multiple transporter types and compartments reflected in the in vivo measurement.…”
Section: Comparison Of Glutamine Influx With Previously Reported Valuesmentioning
confidence: 65%
“…33 Likewise, DON significantly inhibited cell swelling caused by ammonia in cultured astrocytes. 33 It should be emphasized that part of the glutamine synthesized in astrocytes is transported into mitochondria where it is then hydrolyzed to glutamate and ammonia by PAG, 81,82 potentially yielding high levels of ammonia in mitochondria that could trigger OS and the mPT. Such OS and the mPT generated in mitochondria would likely contribute to the astrocyte swelling/brain edema observed in hyperammonemic states.…”
Section: Discussionmentioning
confidence: 99%
“…56 Preliminary studies have also shown a similar attenuation of the MPT, as well as reduction in ROS formation by histidine in cultured astrocytes treated with ammonia. 62 While PAG is clearly present in cultured astrocytes, [63][64][65] its localization in astrocytes in vivo is a matter of controversy. Some immunohistochemical studies have not shown PAG in glia 60,66 ; yet, other immunohistochemical, 67 enzyme histochemical studies, 68 as well as studies using bulk-isolated astrocytes, 69 have all shown a glial localization of PAG.…”
Section: The Trojan Horsementioning
confidence: 99%